2018
DOI: 10.21577/0103-5053.20180034
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Beta-Lactams Antibiotics through Zero-Valent Copper Nanoparticles

Abstract: The removal of the beta-lactam antibiotics (ceftriaxone and cefadroxil) through zero-valent copper nanoparticle (nZVC) was studied in this work. Excellent removal degrees (> 85%) were obtained for both analytes in only 20 min of reaction. Studies were performed in both oxic and anoxic conditions, and in the presence of t-butyl alcohol (TBA), an inhibitor of radicals. The results did not show significant changes. Therefore, the hydroxyl radicals are not the main species responsible for the removal. Total organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…Zero-valent copper (ZVC) has also been used for the removal of various contaminants, such as hexavalent chromium [151], different toxic chlorinated organic compounds [152][153][154], dyes [155,156], and antibiotics [157].…”
Section: Zero-valent Coppermentioning
confidence: 99%
“…Zero-valent copper (ZVC) has also been used for the removal of various contaminants, such as hexavalent chromium [151], different toxic chlorinated organic compounds [152][153][154], dyes [155,156], and antibiotics [157].…”
Section: Zero-valent Coppermentioning
confidence: 99%
“…7) (Table 3). Oliveira et al (2018) studied the nZVC for the removal of cefadroxil 34 and ceftriaxone 35 antibiotics from aqueous solution under oxic and anoxic conditions. More than 85% of the antibiotics were removed within a reaction time of 20 min.…”
Section: Removal Of Drugsmentioning
confidence: 99%
“… Oliveira et al. (2018) studied the nZVC for the removal of cefadroxil 34 and ceftriaxone 35 antibiotics from aqueous solution under oxic and anoxic conditions.…”
Section: Applications Of Nzvc For Environment Remediationmentioning
confidence: 99%
See 1 more Smart Citation
“…Oliveira et al [150], investigated the removal of beta-lactam antibiotics "Cefadroxil and Ceftriaxone" by zerovalent Cu NPs. The study showed excellent removal rates (> 85%) for both antibiotics in only 20 min.…”
Section: Adsorption Propertiesmentioning
confidence: 99%